Association of Specific Antiphospholipid Antibodies to Platelet Count and Thrombocytopenia - Griem, Katharina; Falter, Tanja; Hollerbach, Anne; Jurk, Kerstin; Aboulmaouahib, Brahim; Weinmann-Menke, Julia; Müller-Calleja, Nadine; Lackner, Karl J. (Thrombosis and Haemostasis, 2025)
Background Thrombocytopenia is one of the most common manifestations of the antiphospholipid syndrome (APS). However, its causes are still poorly defined. We have shown recently that antiphospholipid antibodies (aPL) directed against β2-glycoprotein I (β2GPI) of the IgG isotype induced platelet activation and aggregation while aPL directed against cardiolipin and anti-β2GPI IgM had no effect. Since platelet activation by anti-β2GPI might lead to platelet consumption and lower platelet count or overt thrombocytopenia, we analyzed the association of aPL with platelet count.Material and Methods Data of consecutive patients with test orders for anticardiolipin IgG/IgM and anti-β2GPI IgG/IgM and full blood count in our laboratory from August 2015 to April 2019 were analyzed.Results We identified 2,815 individual patients (mean age 45.7 years; 71.1% women) with complete data on aPL and platelet count, of which 445 individuals (mean age 41.0 years; 75.3% women) showed increased aPL titers. Patients with anti-β2GPI of the IgG isotype had significantly lower platelet count (220 ± 84 versus 264 ± 90 G/L, p < 0.0001) and higher frequency of thrombocytopenia (platelet count <100 G/L; 12.2% versus 2.4%, p < 0.005) than patients negative for all four aPL. These differences could not be explained by comorbidities or medications. Neither anticardiolipin IgG nor aPL of the IgM isotype was associated with lower platelet count or thrombocytopenia.Conclusion The exclusive association of anti-β2GPI IgG aPL with low platelet count coincides with its unique ability to activate platelets and induce aggregation in vitro. This supports the hypothesis that anti-β2GPI IgG aPL may induce thrombocytopenia by chronic platelet consumption in vivo.
Keywords: antiphospholipid antibodies; platelet count; thrombocytopenia